Chapter 1 BETTER THEORY, METHODS, AND PRACTICE THROUGH COMPUTATIONAL MODELING - Vancouver, Jeffrey B. (Taylor & Francis, 2024)
This chapter is designed help motivate the current readers' interest in computational modeling as the authors provide a description of the myriad of values computational modeling can bring to our science. Readers are also given a brief history of computational modeling as it relates to the field of I-O psychology. This is followed by a more complete description of the goals for the book, as the authors describe the learning objectives for various levels of computational model afficionados, from the scholarly consumers to the computational model creators. Finally, an overview of the chapters is provided.